Method for evaluating thrombin concentration based on the data of monitoring the viscoelastic properties of native blood in the process of hemocoagulation - Demkin, V. P. 1950-; Melnichuk, S. V.; Demkin, O. V.; Kotlovskaya, L. Yu; Rudenko, T. V.; Tsibulina, A. O.; Zhukovskaya, A. A.; Tyutrin, I. I.; Udut, Vladimir V. (Russian physics journal)
The process of native blood coagulation was studied with the resonant-acoustic method using the technology of low-frequency piezothromboelastography. It is shown that the experimental curve of time dependence of the piezoelectric sensor signal amplitude reflects the change in the rheological properties of blood during coagulation. A formula is obtained that relates the change in the concentration of thrombin to the rate of change in the complex coefficient of blood viscosity. A method has been developed for assessing thrombin concentration during fibrinogenesis based on the technology of piezothromboelastography using a resonant-acoustic method for determining the viscoelastic properties of whole blood. The results of calculating the thrombin concentration by this method are compared with the results of the thrombin generation test.